Main Character’s Speech Functions Analysis In The Movie “Turning Red” - Luh Angelique Vironica Wardhana; Sang Ayu Isnu Maharani (FKIP, Universitas Palangka Raya, 2023)
The study entitled “An Analysis of The Main Character's Speech Functions in The Movie